First record ofScyphophorus acupunctatus (Coleoptera Curculionidae) in Italy (Bollettino di zoologia agraria e bachicoltura, 2024)
Scyphophorus acupunctatus Gyllenhal, first record for Italy, was collected in a greenhouse of Beaucamea recurvata (Lem.) in Lombardy.
Keywords: Scyphophorus acupunctatus; Coleoptera Curculionidae; Italy; Beaucarnea recurvata